2002
DOI: 10.1046/j.1365-2915.2002.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a simulation model for blowfly strike of sheep

Abstract: Abstract. A comprehensive simulation model for sheep blowfly strike due to Lucilia sericata (Meigen) (Diptera: Calliphoridae), which builds on previously published versions but also incorporates important new empirical data, is used to explain patterns of lamb and ewe strike recorded on 370 farms in south-west, south-east and central England and Wales. The model is able to explain a significant percentage of the variance in lamb strike incidence in all four regions, and ewe strike in three of the four regions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The relationship between L. sericata abundance, host susceptibility and strike incidence has been suggested by simulation modelling (Wall et al , 2002), but not previously demonstrated empirically in U.K. sheep grazing systems. Its demonstration here is therefore an important step, because it has many implications for understanding strike incidence patterns and thus optimizing the management of this disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The relationship between L. sericata abundance, host susceptibility and strike incidence has been suggested by simulation modelling (Wall et al , 2002), but not previously demonstrated empirically in U.K. sheep grazing systems. Its demonstration here is therefore an important step, because it has many implications for understanding strike incidence patterns and thus optimizing the management of this disease.…”
Section: Discussionmentioning
confidence: 97%
“…The pattern of strike incidence and its relationship with fly abundance and climatic factors in the U.K. has been explored theoretically using simulation models (Wall et al , 2000, 2002). These models have predicted that, in the early stages of the blowfly season when overwintered L. sericata first emerge, the incidence of strike may be dependent primarily on the relatively low abundance of L. sericata .…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the aetiology of sheep strike is complex and results from the interaction between fly abundance and sheep susceptibility, both of which are, in turn, affected by weather, geography and animal husbandry factors, such as flock size, breed, age class, the timing of shearing and the complex interactions between worm burden, faecal soiling and anthelmintic use (Wall et al , 2002; Broughan & Wall, 2007a, 2007b). Insecticides remain the primary approach used by sheep farmers to prevent unacceptable levels of strike and animal suffering.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible therefore that further improvements might be made if the basic model was re-fitted using revised and/or additional susceptibility functions, particularly in relation to drenching. In a simulation model of flystrike in the U.K., Wall et al (2002) used a combination of seasonal changes in fleece length plus data on nematode egg counts in the faeces of untreated sheep to model susceptibility to breech strike in ewes and lambs. In effect, this is similar to the procedures adopted in the current study, where susceptibility was judged on the basis of progressive temporal changes in faecal and/or urine stain following crutching or shearing.…”
Section: Termsmentioning
confidence: 99%